Ultrases Dalgasının Cevher Hazırlama ve Zenginleştirme İşlemlerinde Uygulamaları - Eşmeli, Kiraz (Soner ÖZGEN, 2024)
Ultrases dalgası, maddesel bir ortama ihtiyaç duyarak insan işitme limitinin üzerindeki frekanslarda yayılan bir ses dalgasıdır. Ultrases dalgası sıvılar içerisinde yayıldığında kavitasyon adı verilen kabarcıklar oluşturur. Kavitasyon kabarcıkları ultrasonik işlemin en önemli özelliğidir. Ultrases dalgası, endüstrinin birçok alanında kullanılmasının yanısıra cevher hazırlama ve zenginleştirme de kullanım alanı bulmuştur. Ultrases dalgası başta flotasyon olmak üzere öğütme, liç, katı-sıvı ayrımı, aglomerasyon, flokülasyon gibi cevher hazırlama ve zenginleştirme proseslerinde kullanılmıştır. Literatürde ultrasonik işlem farklı cihazlar, frekanslar, yöntemler kullanılarak flotasyonun değişik aşamalarında ve farklı minerallerin flotasyonunda uygulanmıştır. Flotasyon ile yapılan çalışmaların çoğu kömür flotasyonu üzerine yapılmıştır. Bu çalışmada ultrases dalgalarının özellikleri detaylı olarak incelenmiştir. Ayrıca, literatürde yer alan ultrasonik işlemin cevher hazırlama ve zenginleştirme proseslerinde kullanımı ile ilgili daha önceki çalışmalar derlenmiş ve sonuçları yorumlanmıştır.

Ultrasound, a sound wave that spreads at frequencies above the human hearing limit, requiring a material medium. When ultrasound is propagated in liquids, it creates bubbles called cavitation. Cavitation bubbles are the most important characteristic of ultrasonic processing. In addition to being used in various fields of industry, ultrasonics has also found application in ore preparation and mineral processing. Ultrasound is a sound wave that propagates at frequencies above the limit of human hearing and requires a material medium. When ultrasound is propagated in liquids, it creates bubbles called cavitation. Cavitation bubbles are the most important characteristic of ultrasonic processing. In addition to being used in various fields of industry, ultrasonics has also found application in ore preparation and enrichment. Ultrasonic processing has been used in ore preparation and enrichment processes such as flotation, grinding, leaching, solid-liquid separation, agglomeration, and flocculation. In the literature, ultrasonic processing has been applied to different stages of flotation and flotation of different minerals using different devices, frequencies, and methods. Most of the studies on flotation have been conducted on coal flotation. In this study, the properties of ultrasound waves were studied in detail. In addition, previous studies on the use of ultrasonic processing in ore preparation and enrichment processes in the literature have been compiled and their results have been interpreted.
Applications of Ultrasound Wave in Mineral Preparation and Processing
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer)